Absentismo laboral (2019)
This document describes and identifies the causes that influence absenteeism, it is also going to present the most critical and common problems of work absenteeism for young people between 20 and 30 years of age, during the document the source of the problematic and thus conclude by means of characteristics in the personnel to be linked where the company must carry out an analysis at the time of hiring its male staff and thus decreasing the rate of absenteeism from work.